1905
DOI: 10.1086/328645
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to the Life History of Apocynum androsaemifolium

Abstract: IT appears that not one of the Apocynaceae, a family of about iooo species, has ever been studied carefully in reference to the minute morphology of the flower. Considering this in connection with the fact that the family stands near the Asclepiadaceae, with their peculiar pollen and stigma, it was believed that it deserved investigation. Buds and flowers of Apocynum androsaernijolium L. were collected in various stages, and the results of their investigation are herewith described.The order of appearance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1937
1937
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In the majority of the Apocynaceae the simultaneous pollen mother cell division is predominant. Frye and Blodgett (1905) observed this in Apocynum, Tackholm and Soderberg (1918) in Vinca, Rau (1940) in Cerhera and Vallaris Mey iported in In the Periplocoideae of the Asclepiadaceae, the simuhaneous pollen cell division is predominant just as in Apocynaceae. The resulting tetrads are usually tetrahedral and isobilateral depending on the direction of the second meiotic spindle.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the majority of the Apocynaceae the simultaneous pollen mother cell division is predominant. Frye and Blodgett (1905) observed this in Apocynum, Tackholm and Soderberg (1918) in Vinca, Rau (1940) in Cerhera and Vallaris Mey iported in In the Periplocoideae of the Asclepiadaceae, the simuhaneous pollen cell division is predominant just as in Apocynaceae. The resulting tetrads are usually tetrahedral and isobilateral depending on the direction of the second meiotic spindle.…”
Section: Discussionmentioning
confidence: 87%
“…Several morphologists have investigated this problem â€" Frye (1901), Gager (1902), Richharia (1934) and others â€" but almost all agree that there is no evidence provided by ontogenetic studies of several genera. Engler (1876) came to the empiric conclusion that only the anterior locules are developed and believed that the posterior locules become diverted to the formation of the hyaline appendage of the anthers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that A. orientalis prefers slightly alkaline, sandy-loamy soils, saltys, mid-calcareous, with poor organic material, and very rich in iron and magnesium (Özen 2006). The noteworthy contributions to the embryological studies of the Apocynaceae were made by Fyre and Blodgett (1905), Guignard (1917), Anderson (1931), Schnarf (1931), Meyer (1938) and Rau (1940). While summarizing the embryological data on Apocynaceae, Davis (1966) mentioned the controversy concerning the nature of division of microspore mother cells, and due to the occurrence of different types of embryogeny Apocynaceae was termed a heterogeneous group by Maheshwari in 1971.…”
Section: Introductionmentioning
confidence: 99%
“…Hier ist eine Untersuchung von FRYE und BLODGETT (1905) bei Apocynum androsaemifolium ausge fuhrt worden; auf Tafel II, Figur 8 wird eine sukzedane Teilungs figur abgebildet.…”
unclassified